Agroclimatic and agroecotoxicological justification of zonal chemical protection systems against harmful organisms for field crops under conditions of climate change in Ukraine - Borzykh, O.; Bublyk, L.; Chaika, V.; Gavrylyuk, L.; Kruk, I.; Shevchuk, O.; Neverovska, T.; Bakhmut, O. (Quarantine and plant protection, 2022)
Goal. Agroclimatic and agroecotoxicological zoning of the territory of Ukraine in order to justify ecologically safe zonal systems of chemical protection against harmful organisms, their optimization and adaptation to changes in climatic conditions and phytosanitary state of agrocenoses in different soil-climatic zones of Ukraine. Methods. Analytical-synthetic and experimental methods were used in the research. Literary sources, reports of the Institute of Plant Protection, data on the distribution and number of pests given in the annual reviews of the Department of Phytosanitary Safety of the State Service of Ukraine on Food Safety and Consumer Protection, databases of the State Statistic Service and the Hydrometeorological Center of Ukraine, as well as the results of field experiments were analyzed. Phytosanitary and ecotoxicological monitoring was carried out according to generally accepted methods. The degree of hazard of pesticide use was assessed using an integral 7-point scale, the risk — according to the agro-ecotoxicological index (AETI). Results. Ecological and statistical analysis of long-term databases, dynamics of agrometeorological indicators allows us to come to the conclusion that during the last 10 years climate changes have accelerated. They manifested through the equalization of the temperature field across the country, the increase in the sum of effective temperatures, and a deterioration of heat and moisture supply. This led to a disruption in the functioning of agrocenoses, a decrease in tolerance to the pesticide load. Under conditions of extension of the specified trends, significant disruptions in the functioning of the agricultural sector should be expected, considering the speed of changes. With the help of the Arc GIS — Arc INFO software complex, the agroclimatic and agroecotoxicological zoning of the territory of Ukraine under conditions of climatic changes of 2010—2020 was carried out. A decrease in the self-cleaning ability of the territory has been established. This is especially noticeable in the Forest Steppe, where the zonal self-cleaning index decreased from 0.70—0.50 to 0.60—0.45. Maps of agro-climatic zones and regions of Ukraine with different self-cleaning capabilities have been created. Conclusions. Regular addition and update of agro-climatic regulatory information under conditions of climate change is used for the correct selection and placement of agricultural areas, crops, assessment of conditions for their growth and development, planning of field work periods, forecasting of crop production in a specific year. This information is necessary for improving the culture of agriculture, increasing the production of plant products along with the wide application of modern technologies of crop cultivation, in particular chemical protection against harmful organisms.